PENGARUH PENYULUHAN KESEHATAN REPRODUKSI TERHADAP PENGETAHUAN DAN SIKAP SISWI DI SMP NEGERI 20 MALUKU TENGAH - Petriana Mahmud; Ririn Kamelia Batuwael (STIKES Pasapua Ambon, 2022)
Introduction: Adolescence is a period of transition from childhood to adulthood which is marked by various changes including physical, psychological, and social changes. Adolescent knowledge about reproductive health is still very low. Many surveys that have been conducted in developing countries show that nearly 60% of pregnancies in women under the age of 20 are mistimed or unwanted. Methods: The research method used was an experimental design. The research sample was taken using an acendal sampling research technique with a total sample of 30 respondents. Bivariate analysis using paired t-test. Results: The results of this study were that some of the middle school students of SMP Negeri 20 Maluku were in the category of prior knowledge, namely 20 (66.7%) and 10 (33.3%) of respondents and the category of knowledge after, namely 28 (93.3%) and 2 (6,7) respondents. While the previous attitude categories were 19 (63.3%) and 11 (36.7%) respondents and the post attitude categories were 27 (90.0%) and 3 (10.0%) respondents. There is an effect of reproductive health counseling on increasing knowledge and attitudes of female students at SMP Negeri 20 Central Maluku with the result (p<0.05). Conclusion: there is an effect of counseling on the effect of reproductive health counseling on increasing knowledge and attitudes in female students of SMP Negeri 20 Central Maluku.